Characteristics of Yoghurt Drink With Addition of Sweet Starfruit Extract (Averrhoa carambola) - Anggi Indah Yuliana; Vindia Nur Azlina; Miftachul Chusnah (AGARICUS: Advances Agriculture Science & Farming, 2022)
Sweet star fruit (Averrhoa carambola) is a horticultural product that is rich in fiber, potassium, phosphorus, and vitamin C. Sweet star fruit can be processed into derivative products to increase economic value, one of which is a yogurt drink. This study aimed to determine the effect of adding the concentration of sweet star fruit extract in yogurt drink on the characteristics of yogurt drink which includes organoleptic tests, pH, and total lactic acid bacteria. The organoleptic assessment in this study used a non-factorial Completely Randomized Design with treatments K0: without sweet star fruit extract, K1: addition of 5% star fruit extract, K2: addition of 10% sweet star fruit extract, and K3: addition of star fruit extract sweet 15%. Analysis of pH value and total lactic acid bacteria was carried out on all yogurt drink treatments. The results showed that yogurt drink with the addition of sweet star fruit extract 0%, 5%, 10%, and 15% did not have a significant effect on the organoleptic characters, namely the taste, smell, color, and texture of the yogurt drink. The higher the concentration of sweet star fruit extract in the yogurt drink increased the pH value but the total lactic acid bacteria contained in the yogurt drink was decreased.